Faktor dan Dampak Pemberian Vaksin Palsu bagi Anak Balita - Nursabriani Umar (IAIN TERNATE, 2022)
Vaccines are antigens in the form of microorganisms that are dead, still alive but attenuated, still intact or parts thereof, which have been processed, in the form of toxin microorganisms that have been processed into toxoids, recombinant proteins given to a person will cause active specific immunity against certain infectious diseases. Management of Vaccine Production is often of quality and storage according to the standards set by Health Number 42 of 2013 concerning implementation, ultimately it is difficult for consumers to get a proper picture of the products circulating in the market and hospitals. The results of the research on the factors of giving fake vaccines to babies are the lack of vaccine production in Indonesia with the demand for hospitals, clinics and pharmacies for cheap vaccines also being a factor in giving fake vaccines to toddlers. Manufacturers and distributors of fake vaccines take advantage of opportunities when there is a shortage of stock from authorized distributors. The impact of giving fake vaccines is the inappropriateness of the process and ingredients of fake vaccines can have a bad impact on children under five in the short term and are susceptible to disease and in the long term.